Voltage-assisted capillary LC of peptides using monolithic capillary columns prepared by ring-opening metathesis polymerization - Sedláková, Pavla; Miksik, Ivan; Gatschelhofer, Christina; Sinner, Frank M; Buchmeiser, Michael R (Electrophoresis, 2007)
We examined the use of monolithic capillary columns prepared via ring-opening metathesis polymerization (ROMP) for peptide separation in voltage-assisted capillary LC (voltage-assisted CLC). In order to demonstrate their potential for peptide separation, ROMP-derived monoliths with RP properties were prepared. The preparation procedure of monoliths was transferred from ROMP monoliths optimized for CLC. ROMP monoliths were synthesized within the confines of 200 microm id fused-silica capillaries with a length of 37 cm. After optimization of the chromatographic conditions, the separation performance was tested using a well-defined set of artificial peptides as well as two peptidic mixtures resulting from a tryptic digest of BSA as well as a collagenase digest of collagen. ROMP monoliths showed comparable performance to other monolithic separation media in voltage-assisted CLC published so far. Therefore, we conclude that by optimizing the composition of the ROMP monoliths as well as by using the controlled manner of their functionalization, ROMP monoliths bear a great potential in CLC and CEC.
Keywords: Cattle; Oligopeptides; Animals; Capillary Electrochromatography; skot; trypsin; kolagenasy; Collagen; Polymers; sérový albumin hovězí; kolagen; oligopeptidy; Serum Albumin, Bovine; kapilární elektrochromatografie; peptidové fragmenty; Collagenases; peptidy; Peptide Fragments; polymery; Trypsin; zvířata; Peptides